The Unified Medical Language System - Lindberg, D. A. B.; Humphreys, B. L.; McCray, A. T. (Methods of Information in Medicine, 1993)
In 1986, the National Library of Medicine began a long-term research and development project to build the Unified Medical Language System® (UMLS®). The purpose of the UMLS is to improve the ability of computer programs to “understand” the biomedical meaning in user inquiries and to use this understanding to retrieve and integrate relevant machine-readable information for users. Underlying the UMLS effort is the assumption that timely access to accurate and up-to-date information will improve decision making and ultimately the quality of patient care and research. The development of the UMLS is a distributed national experiment with a strong element of international collaboration. The general strategy is to develop UMLS components through a series of successive approximations of the capabilities ultimately desired. Three experimental Knowledge Sources, the Metathesaurus®, the Semantic Network, and the Information Sources Map have been developed and are distributed annually to interested researchers, many of whom have tested and evaluated them in a range of applications. The UMLS project and current developments in high-speed, high-capacity international networks are converging in ways that have great potential for enhancing access to biomedical information.
Keywords: Unified Medical Language System; UMLS; Semantic Network; National Library of Medicine; NLM; Telecommunication; Information Management; IAIMS